Letters to His Son, 1759-65 : On the Fine Art of Becoming a Man of the World and a Gentleman - Chesterfield, Philip Dormer Stanhope, Earl of, 1694-1773 (Salt Lake City, UT : Project Gutenberg, 2004)
"Letters to His Son, 1759-65" by Earl of Philip Dormer Stanhope Chesterfield is a collection of correspondence written in the mid-18th century. The letters serve as guidance for the Earl's son, addressing various aspects of life, politics, manners, and the art of becoming a well-rounded gentleman in society. The opening of the book introduces the Earl as he wishes his son well in a series of letters filled with personal anecdotes and political musings. He discusses health matters, current news from London, and provides insights into societal expectations and etiquette. The letters are marked by Chesterfield's witty observations about people's behaviors and the intricacies of aristocratic life, offering a peek into the concerns of a father wanting to equip his son with the skills necessary to navigate the complexities of the world. (This is an automatically generated summary.)
Release date is 2004-12-01
Produced by David Widger
Keywords: Conduct of life